Desenvolvimento em ASP.NET MVC, JQuery e AJAX - Cherubini, Edivaldo Negir (2011)
With the interest of creating more interactive web applications, agile and productive, more importance has been given to the frameworks and plugins. The JQuery, for example, simplify the Javascript code, aims to get developers to produce more in less time. All this using the AJAX web application to be closer and closer to a desktop application and run faster than a normal web application. JQuery only makes the work of the client, when you need to send the form data is necessary to have a robust architecture that can maintain and manipulate the data with greater freedom. The ASP.NET MVC also divides the application into three layers facilitating the understanding of the logic of the system and allows that the developer handle HTTP protocols with greater freedom. This work focuses on describing the concepts and capabilities of the technologies ASP.NET MVC, JQuery and AJAX. And through a case study demonstrate the productivity gains and benefits that the technology offered in web application development.